PENGARUH PENGGUNAAN MEDIA ANIMASI NUSSA DAN RARA TERHADAP KETERAMPILAN MENYIMAK ANAK KELOMPOK B DI TK SUKA CERIA MENDO - Eriska, Lenny; Rachmayani, Ika; Musaddat , Syaiful (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to find out the effect of using Nussa and Rara animation media on the listening skills of group B children at TK Suka Ceria Mendo. The type of research used is quantitative research with an experimental method and a One Group Pretest-Posttest Design. The research sample consisted of 12 children from group B2 at TK Suka Ceria Mendo. Data collection techniques used observation and documentation. The data obtained were analyzed using the Shapiro-Wilk normality test, Levene's Test for homogeneity, and the Paired Sample T-Test. The normality test results showed a pretest significance value of 0.267 and a posttest value of 0.260, meaning the data were normally distributed. The homogeneity test results showed a significance value of 0.110, which means the data are homogeneous. Next, the results of the hypothesis test using the Paired Sample T-Test showed a significance value (2-tailed) of 0.000 < 0.05, which means there is a significant difference between the pretest and posttest results of the children's listening skills. Therefore, H₀ is rejected and Hₐ is accepted. This means that using the Nussa and Rara animation media has a significant effect on the listening skills of Group B children at TK Suka Ceria Mendo. The results of this study show that the Nussa and Rara animation media can be used as one of the effective learning media alternatives to support the development of early childhood listening skills.